Convexity Preserving Integral Operator (Journal of Humanitarian and Applied Sciences, 2023)
The purpose of this paper is to determine the conditions of an integral operator given by (1) to be convex.
Keywords: and phrases; Analytic function; integral operator; convex function; close-to-convex function